The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/rheumatology/kep419
|View full text |Cite
|
Sign up to set email alerts
|

Spinal inflammation lesions as detected by magnetic resonance imaging in patients with early ankylosing spondylitis are more often observed in posterior structures of the spine

Abstract: Inflammatory MRI lesions in early AS are seen more often in posterior structures of the spine. This may be relevant for the diagnosis of early AS and the early detection of inflammatory spinal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 18 publications
0
14
2
1
Order By: Relevance
“…The 17% positive patients at baseline in our study are different from previous reports, which found inflammation at this site in a higher percentage of patients 38 39…”
Section: Discussioncontrasting
confidence: 99%
“…The 17% positive patients at baseline in our study are different from previous reports, which found inflammation at this site in a higher percentage of patients 38 39…”
Section: Discussioncontrasting
confidence: 99%
“…In established AS with longer disease duration, involvement of posterior elements was described in up to 87% of patients affected 32. Our findings are in contrast to a recent publication by Bochkova et al ,33 where much higher frequencies of posterior element involvement, especially in cases of early SpA, was reported (figure 2). …”
Section: Discussioncontrasting
confidence: 95%
“…recently demonstrated that about half of their 27 patients with non‐radiographic SpA had evidence of erosions in the sacroiliac joints on MRI. Bochkova et al . recently found that AS patients with short disease duration had frequent involvement of the posterior elements of the spine compared to the vertebral bodies.…”
Section: Diagnostic Criteriamentioning
confidence: 99%